Public Memory, Architectural Language, and Its Configurational Relationship in the Memorial Museum: A Case Study of the War Memorial of Korea Using Space Syntax and Movement Tracking - Jae Hong Lee (Buildings, 2024)
Memorial museums serve as a record of the past and provide evidence of the past; moreover, they are a place for remembering the past and healing the present. In particular, their architectural language, such as movement through space, is actively involved in fostering public memory that implies a shared understanding of the past. However, it is hardly explained how public memory is configured in memorial museums, and how it is experienced by the act of moving around within the places. This study, hence, aims to investigate the configurational relationship between public memory and movement through space throughout an in-depth case study using visibility graph analysis as one of space syntax techniques, and movement tracking analysis. By examining the War Memorial of Korea, which is dedicated to commemorate sacrifices during the Korean War in memorial halls and chronologically describes wars in the Korean Peninsula, it was found out that a memorial museum works in a bifurcated way. Its spatial layout leads to a locally focused experience along a strongly structured commemorative sequence. On the contrary, it allows globally dispersed spatial experiences to take place along the integration core, suggesting both specific and wide-ranging themes and contents throughout their various exhibitions. Therefore, the locally focused paths elicit a commemorative experience by adding depth, whereas the globally dispersed paths bring about informal itineraries that start from their integration cores. It concludes that spatial configurations, as a non-verbal language, plays a role in transmitting the public memory.